PEMBENARAN IMAN DALAM PERSPEKTIF PAULUS DAN IMPLEMENTASINYA TERHADAP IMAN GEREJA MASA KINI - Jefri Paranni; Insal Erwin, Mesak Boba, Tomi (ADISAM PUBLISHER, 2023)
This research aims to analyze the concept of faith renewal from the perspective of the Apostle Paul, one of the central figures in the early development of Christianity, and how this concept can be implemented in the context of contemporary church faith. This study utilizes bibliographic research methods and textual analysis to comprehend Paul's thoughts on faith and explore its relevance in the present-day Church context. Through his letters in the New Testament, the Apostle Paul developed a rich perspective on faith in relation to grace, righteousness, and sanctification. He also portrayed faith as the foundation of an individual's relationship with God and as the basis of the church community. This study will dissect Paul's theology of faith, including the concept of justification by faith and the significant role of grace in achieving salvation. Furthermore, this research will explore ways to implement the concept of faith renewal in the life of today's church, encompassing aspects such as teaching, social services, and spiritual development in the modern church context. The primary question to be answered is how the church can apply Paul's teachings on faith to strengthen and renew the faith of its members in facing the challenges and dynamics of the present era. The results of this research are expected to provide profound insights into the importance of understanding and implementing the concept of faith renewal in the context of the contemporary Church. Additionally, this research is anticipated to offer practical guidance to church leaders, theologians, and church members on integrating Paul's teachings on faith into their daily lives and ministry.